Information seeking behavior of forensic experts in selected investigating institutions in Metro Manila - Gutierrez, Harriette Josephine B. (2010)
This study focused on the information seeking behavior of forensic experts in selected Investigatory Institution in Metro Manila. This study aimed to find out the searching strategies of forensic experts; the types of materials forensic experts prefer to use in searching and as to format; the feelings, behaviors and thoughts they have during the search process, and the issues and concerns of forensic experts in information seeking process.